Dominating Energy in products of intuitionistic fuzzy graphs - Shaik Sharief Basha; A kalimulla; R Vijayaragavan (Journal of Global Pharma Technology, 2017)
The concept of energy of an Intuitionistic Fuzzy Graph is extended to dominating Energy in various products in Intuitionistic Fuzzy Graph. In this paper, We have obtained the value of dominating Energy in different products such as ring Sum, Cartesian Product, Lexicographic Product, Tensor product and Strong Product between two intuitionistic Fuzzy graphs. Also we study the relation between the dominating Energy in the various products in two Intuitionistic Fuzzy Graphs.